PENGARUH PROCEDURAL FAIRNESS, DISTRIBUTIVE FAIRNESS, INTERACTIONAL FAIRNESS, TERHADAP KEPUASAN PELANGGAN - Jatmiko, Robby (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2012)
This study examined three independent variables, ie ProceduralFairness, Distributive Fairness, and Interactional Fairness can affectcustomer satisfaction. The purpose of this study was to determine the effectof the three independent variables on customer satisfaction. This research was conducted with a questionnaire to 100 PLNcustomer obtained by using purposive sampling techniques. The data thathave met the test of validity, reliability, and test the assumptions ofclassical. These results indicate that all the independent variables tested arepositive and significant impact on customer satisfaction through the F testand t test, whereas the number Adjusted R Square of 0.236 indicates23,60%of the variation in people satisfaction which can be explained bythe third independent variable, where the remaining 76.40% is explainedby other factors outside of the study